EVALUATION OF EXTENDED ELASTIC IMPEDANCE INVERSION AND SEISMIC MULTIATTRIBUTE TO IDENTIFY THE LITHOLOGY AND FLUID DISTRIBUTION IN A SANDSTONE RESERVOIR, TALANG AKAR FORMATION - HAMDANI BATUBARA (NIM : 12307065), ARDI
Talang Akar is a silici-clastic formation which is dominated by sandstone and shale. In this field, the formation is proven to produce a siginificant amount of hydrocarbon in several of its wells. This discovery encourages to do an advanced study to characterized the reservoir to find new locations for the well to produce optimally. Reservoir in this formation is known to be thin layers of sandstone inside a dominant shale body. Thickness of sandstone intervals are below the seismic tuning resolution. The physical character of sandstone and shale which is defined by its modulus, are different between the two wells used to analyze. The two condition mentioned above limits the ability of the seismic to characterize the reservoir using inversion. Extended Elastic Impedance (EEI) which is an extended version of Elastic Impedance (EI) is discovered has the ability to correlate well with modulus 𝜇𝜇𝜌𝜌, 𝜆𝜆𝜌𝜌, and Vp/Vs ratio in a certain angle of its projection in this field. The result of EEI Inversion is then used as an external attribute in an analysis of multi-attribute with a log target of Gamma-Ray (GR) and Water Saturation (SW). The result of the application of seismic multi-attribute is capable of delineating the distribution of sandstone and shale, and then show the potential hydrocarbon-saturated area in the formation using its pseudo-GR and pseudo-SW.